2014
DOI: 10.1007/s10067-013-2452-7
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for acute rheumatoid arthritis patients who have had an inadequate response to disease-modifying antirheumatic drug (DMARD): a systematic review and meta-analysis

Abstract: The aim of this systematic review and meta-analysis is to assess the efficacy and safety of tofacitinib for the treatment of patients with acute rheumatoid arthritis (RA) who have had an inadequate response to disease-modifying antirheumatic drug (DMARD). Randomized controlled trials were searched in MEDLINE (1966-2013), Embase (1947-2013), the Cochrane Central Register of Controlled Trials (1948-2013), WHO International Clinical Trial Registration Platform (2004-2013), Clinical Trial.gov (1999-2013), and Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Ruxolitinib™ treatment substantially reduced spleen size and improved quality of life in a significant proportion of patients with myelofibrosis but, surprisingly, treatment was also effective in patients without mutated JAK2 and there was not convincing evidence of reduction in mutated allele burden or progression to AML [58, 59]. Tofacitinib™ was more effective in improving symptoms in rheumatoid arthritis than placebo or existing anti-TNF receptor therapy [60]. While some of these results are promising, it is clear that a better understanding of the specificity of JAK inhibitors is required to draw firm conclusions about optimal therapies for these diseases.…”
Section: Jak Mutations In Human Diseasementioning
confidence: 99%
“…Ruxolitinib™ treatment substantially reduced spleen size and improved quality of life in a significant proportion of patients with myelofibrosis but, surprisingly, treatment was also effective in patients without mutated JAK2 and there was not convincing evidence of reduction in mutated allele burden or progression to AML [58, 59]. Tofacitinib™ was more effective in improving symptoms in rheumatoid arthritis than placebo or existing anti-TNF receptor therapy [60]. While some of these results are promising, it is clear that a better understanding of the specificity of JAK inhibitors is required to draw firm conclusions about optimal therapies for these diseases.…”
Section: Jak Mutations In Human Diseasementioning
confidence: 99%
“…These findings are similar to findings reported in prior meta-analyses, but this review includes all patient-centered outcomes mentioned in the studies reviewed and also includes data from more recent studies. 14 , 16 Measurements of patient’s pain and global assessment of disease demonstrated that tofacitinib 5 mg bid was more effective than both placebo and tofacitinib 1–3 mg bid in both monotherapy and combination therapy studies.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of anti‐TNFα and MTX had a better response than anti‐TNFα alone, despite certain anti‐TNFα being suggested as monotherapy . Tofacitinib in active RA patients with inadequate response or intolerance to csDMARDs showed similar results to bDMARDs . Etanercept, tocilizumab and tofacitinib are very effective in reducing signs and symptoms even when used as monotherapy.…”
Section: Recommendationmentioning
confidence: 98%